A modified HJC model for improved dynamic response of brittle materials under blasting loads. (July 2020) - Liu, Kai; Wu, Chengqing; Li, Xibing; Li, Qiyue; Fang, Jianguang; Liu, Jian
Abstract: The original Holmquist-Johnson-Cook (HJC) model, which can only capture the compressive behaviour but not the tensile behaviour of brittle materials, is modified in this study. First, the Lode-angle function is introduced to the yield strength surface to consider the changes in the substantial shear strength between the tensile and compressive meridians. A hyperbolic function is used to describe the strain rate effect under dynamic tensile loading. An exponential model is introduced to express the tensile softening stage of brittle material and define the tensile damage variable. Then the modified HJC model is implemented in LS-DYNA via user subroutine UMAT. Further the modifications are validated by single element tests and rock mechanical laboratory experiments. The verification results show that the modified HJC model can effectively describe the tensile responses of brittle material under static and dynamic loading. Last, a comparison between a blasting-crater field test and the corresponding numerical prediction by the modified HJC model is carried out. The comparison results demonstrate that the shape and size of the crater predicted by the modified HJC model show a good agreement with the field test data. Therefore, the modified HJC model has the capacity to capture the tensile and compressive behaviours and damage evolution of brittle material.